If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9x + -5 = 9 + -2x Reorder the terms: -5 + -9x = 9 + -2x Solving -5 + -9x = 9 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -5 + -9x + 2x = 9 + -2x + 2x Combine like terms: -9x + 2x = -7x -5 + -7x = 9 + -2x + 2x Combine like terms: -2x + 2x = 0 -5 + -7x = 9 + 0 -5 + -7x = 9 Add '5' to each side of the equation. -5 + 5 + -7x = 9 + 5 Combine like terms: -5 + 5 = 0 0 + -7x = 9 + 5 -7x = 9 + 5 Combine like terms: 9 + 5 = 14 -7x = 14 Divide each side by '-7'. x = -2 Simplifying x = -2
| -16/3/2/3 | | 2m/n-5m/3n | | 3y-2=6-y | | .5(6x+4)=4x-9 | | -51/3x/2/3 | | 15(b+6)-9b= | | 3x^4+19x^3+6x^2=0 | | 2p^2+21p+40=0 | | -56=a^2+18a | | 3/4(4x8-8)=-10 | | -6=2a-3 | | 7-8x-3=-65+6x-15 | | 4d+5d=54 | | 11/3x22/5 | | (r^10-1)/(r^30-1) | | x/9+15=19 | | .5x+6-2x+.5=7/2 | | 2k^2+11k-40=0 | | 9+5[a-4(a-5)]= | | 2x+14.4= | | (4x+12)-6=26 | | 26+(-46)+(-26)= | | 2u^2-9u+11=u^2-1 | | 3/2a-8=5/4 | | 8x+2=5x+23 | | 12s+4c=132 | | P+4/p^2-11p+30+p+5/p^2-11+30 | | 3x-6y=20 | | 17+(-7)+(-17)+7= | | 5-(1+3)=-1+2(t-3) | | y/2+5/2=y/4 | | -728-4(-3)= |